Transposable elements as scaffold/matrix attachment regions: shaping organization and functions in genomes - Pathak, Rashmi Upadhyay; Phanindhar, Kundurthi; Mishra, Rakesh K. (Frontiers in Molecular Biosciences, 2024)
The hierarchical structure of eukaryotic genomes has regulatory layers, one of them being epigenetic “indexing” of the genome that leads to cell-type-specific patterns of gene expression. By establishing loops and defining chromatin domains, cells can achieve coordinated control over multi-locus segments of the genome. This is thought to be achieved using scaffold/matrix attachment regions (S/MARs) that establish structural and functional loops and topologically associating domains (TADs) that define a self-interacting region of the genome. Large-scale genome-wide mapping of S/MARs has begun to uncover these aspects of genome organization. A recent genome-wide study showed the association of transposable elements (TEs) with a significant fraction of S/MARs, suggesting that the multitude of TE-derived repeats constitute a class of anchorage sites of chromatin loops to nuclear architecture. In this study, we provide an insight that TE-driven dispersal of S/MARs has the potential to restructure the chromosomes by creating novel loops and domains. The combination of TEs and S/MARs, as elements that can hop through the genome along with regulatory capabilities, may provide an active mechanism of genome evolution leading to the emergence of novel features in biological systems. The significance is that a genome-wide study mapping developmental S/MARs reveals an intriguing link between these elements and TEs. This article highlights the potential of the TE–S/MAR combination to drive evolution by restructuring and shaping the genome.